The Effects of Virtual Reality News on Learning about Climate Change. Issue 1 (2nd January 2022) - Barnidge, Matthew; Sherrill, Lindsey A.; Kim, Bumsoo; Cooks, Eric; Deavours, Danielle; Viehouser, Michael; Broussard, Ryan; Zhang, Jiehua
ABSTRACT: Promoting public knowledge about climate is important for garnering support for climate-change policy, and researchers have begun to study the effectiveness of new technologies as learning tools. News organizations are increasingly producing immersive journalism, including virtual reality (VR) and augmented reality (AR), and this study tests whether VR news can be an effective tool for learning about climate change. Based on results from a controlled, in-person laboratory experiment comparing an immersive VR news story to 360°-video and text-with-images versions, we find no main effects on the learning outcomes. However, we do find indirect effects on cognitive elaboration, which are conditional on preexisting knowledge about climate change. Results are discussed in light of their implications for theory about learning in multimedia environments, as well as their implications for the science of science communication.